Cenozoic marine turtle record from southern South America: New insights from the Miocene of Patagonia, Argentina - Sterli, Juliana (2021)
The study of marine turtles is a challenging topic because of the cosmopolitan nature of its fossil record and current distribution. Thus, it might be difficult to study and compare specimens, but sometimes even the smallest fragments or isolated occurrences might provide significant new information for the whole group. The Cenozoic fossil record of marine turtles (Pan-Chelonioidea) in South America is scarce with less than 10 published occurrences. The southernmost published record corresponds to a fragmentary and undetermined specimen of pan-dermochelyid (MPEF-PV 565) from the lower Miocene Gaiman Formation in Chubut province, Patagonia, Argentina. However, recent fieldwork has significantly increased the record of marine turtles from northeastern Chubut. The fossil record of pan-dermochelyids was increased with two findings from the Gaiman Formation: one fragmentary consisting of two ossicles (MPEF-PV 11360) and an almost complete carapace with associated postcranium (MPEF-PV 10918). Furthermore, also from the Gaiman Formation, a lower jaw of a pan-cheloniid (MPEF-PV 11382) was found. This group was also recently found in the upper Miocene Puerto Madryn Formation, represented by shell and postcranial remains (MPEF-PV 10929) and a skull (MPEF-PV 2577) coming from Gaiman or Puerto Madryn formations. In summary, we can conclude that: (1) the northeastern Chubut presents the most diverse and abundant record of chelonioid turtles in the Atlantic coast of South America; (2) the reported pan-cheloniid specimens expand the stratigraphic and geographic range of the group in the Atlantic coast in the Neogene; (3) the almost complete carapace of a pan-dermochelyid represents one of the most complete specimens of the group found up-to-date in the world. Thus, these new findings will provide valuable information on the anatomy, taxonomy, and diversity of the marine turtles that once populated the southwestern Atlantic sea and coasts of southern South America.